The Analysis of Code-Mixing in an English Learning Platform on Youtube - Niki Saputri; Agus Salim (Sekolah Tinggi Agama Islam Negeri Majene, 2022)
This study aims to determine type of code-mixing and function of code-mixing in English learning platform on YouTube. This study is important because by knowing more about the type and the function of code-mixing, we can have broad knowledge of language use. This study employed a qualitative method because it described a phenomenon under a study. In collecting the data, this study analysis the data (video) by watching. The results of this study are to find out some examples types of code-mixing from Aaron’s English YouTube Channel. There are two types namely intra sentential mixing have two forms specifically word and phrase then extra sentential mixing. Categorizing the code-mixing function from the example of the expression, and there are two functions from the results of this analysis, namely suggestion and emotional expression.